Inovasi dan Teknologi dalam Pemasaran Global untuk Meningkatkan Daya Saing di Pasar Internasional - Khoirul Ashhab; Moh. Wahib (PUTRA JAWA PUBLISHER, 2024)
The main focus of this study is to examine how innovation and technology impact global marketing. As technology and innovation continue to evolve, they play a crucial role in driving competition among companies in the global marketplace. In the context of increasingly fierce competition, companies are required to innovate to create products that meet dynamic consumer needs. The method used in this research is literature study, by collecting, analyzing and synthesizing information from various relevant academic sources. The aim of this research is to identify the role of innovation in increasing competitiveness in international markets. Based on this research, it was found that innovation can improve product quality, productivity, efficiency, and open up new opportunities to create a wider market. However, in implementing this innovation there are also several challenges, such as limited resources and an unsupportive organizational structure.